Successful surgical repair of a massive window duct in a 1-month old with aniridia and pulmonary interstitial glycogenosis. (22nd May 2014) - Siomos, Austine K.; Mitchell, Max B.; Fonseca, Brian M.
Abstract: The window duct is a rare congenital anomaly that is physiologically similar to an aortopulmonary window but is extrapericardial at the distal pulmonary trunk. The diagnosis is challenging, and surgical management is complex. Our patient is the first and the youngest to be reported with successful closure and diagnosed by magnetic resonance imaging.